Extra-/intracellular biosynthesis of gold nanoparticles by an alkalotolerant fungus, trichothecium sp. - Ahmad, Absar; Senapati, Satyajyoti; Khan, Mohammad Islam; Kumar, Rajiv; Sastry, Murali (Journal of Biomedical Nanotechnology, 2005)
The development of reliable, eco-friendly processes for the synthesis of nanoscale materials is an important aspect of nanotechnology. As part of our ongoing investigation into the use of fungi for nanoparticle synthesis, we report herein that depending on the reaction conditions of the fungus Trichothecium sp. with aqueous gold ions, gold nanoparticle synthesis can be controlled to occur either within the biomass or extracellularly. Moreover, we have found that reaction of gold ions with the Trichothecium sp. fungal biomass under stationary conditions results in the rapid extracellular formation of gold nanoparticles of spherical, rod-like and triangular morphology whereas reaction of the biomass under shaking conditions resulted in intracellular growth of the nanoparticles. It is believed that on changing the reaction conditions of the fungus with gold ions, the enzymes and proteins which are being released into the medium under stationary conditions do not get released under shaking conditions resulting in the formation of extracellular or intracellular gold nanoparticles respectively. The gold nanoparticles are not toxic to the cells and the cells continued to grow after the biosynthesis of the gold nanoparticles in both the cases.
Keywords: Biosynthesis; enzymes; Fungus; Gold; Morphology Control; Nanoparticles